The unfolded protein response in multiple sclerosis - Lin, Wensheng; Stone, Sarrabeth (Frontiers in Neuroscience, 2015)
The unfolded protein response (UPR) occurs in response to endoplasmic reticulum (ER) stress caused by the accumulation of unfolded or misfolded proteins in the ER. The UPR is comprised of three signalling pathways that promote cytoprotective functions to correct ER stress; however, if ER stress cannot be resolved the UPR results in apoptosis of affected cells. The UPR is an important feature of various human diseases, including multiple sclerosis (MS). Recent studies have shown several components of the UPR are upregulated in the multiple cell types in MS lesions, including oligodendrocytes, T cells, microglia/macrophages, and astrocytes. Data from animal model studies, particularly studies of experimental autoimmune encephalomyelitis (EAE) and the cuprizone model, imply an important role of the UPR activation in oligodendrocytes in the development of MS. In this review we will cover current literature on the UPR and the evidence for its role in the development of MS.